2006
DOI: 10.1039/b517653k
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of toluene over TiO2–xNx under visible light irradiation

Abstract: We report the photooxidation of toluene over nitrogen doped TiO(2) (TiO(2-x)N(x)) under visible light irradiation. The photocatalytic oxidation of toluene in air over TiO(2-x)N(x) powders was studied using diffuse reflectance Fourier transform infrared spectroscopy (DRIFTS), gas chromatography (GC), ion chromatography (IC), and gas chromatography mass spectrometry (GC-MS), focusing on the photocatalytic decomposition processes of toluene. Results obtained indicate that toluene, weakly adsorbed on the catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 52 publications
0
78
0
Order By: Relevance
“…[75] To find out which decomposition product of urea may be responsible for formation of the final nitrogen species, titania was treated at 400 8C with an equal weight amount of isocyanic acid, cyanamide, melamine or a melem/melon mixture. To simulate the initial urea decomposition products [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…[75] To find out which decomposition product of urea may be responsible for formation of the final nitrogen species, titania was treated at 400 8C with an equal weight amount of isocyanic acid, cyanamide, melamine or a melem/melon mixture. To simulate the initial urea decomposition products [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers attribute the high photocatalytic activity of this preparation to 42 the intimate contact between two phases, enhancing separation of photogenerated 43 electrons and holes, and resulting in reduced recombination [43]. 44 45 …”
Section: Electronic Processes In Tio 2 Photocatalysis 16 17mentioning
confidence: 99%
“…One dimensional 13 (1D) titania nanostructures (nanotubes, nanorods, nanowires, nanobelts, nanoneedles) 14 have been also formed by hydrothermal synthesis but high emphasis was given in titania 15 self-assembled nanotubular films grown by electrochemical anodization on titanium 16 metal foils. Advantages of such structures is their tailored morphology, controlled 17 porosity, vectorial charge transfer [45,46] and low recombination at grain boundaries that 18 result in enhanced performance in photoinduced applications, mainly in photocatalysis 19 [45,47,48]. An interesting use of TiO 2 nanotubes in photocatalytic applications is the 20 growth of freestanding flow-through membranes [45] Indeed these types of reactions are exploited in the well known dye sensitized solar cells 33 [22].…”
Section: Strategies For Improving Tio 2 Photoactivity 46mentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of 2, 4-dichlorophenol with Degussa P-25 and the nitrogen-doped TiO 2 using triethylamine was compared and it was reported that the N-doped exhibited a higher efficiency in the removal of 2, 4-dichlorophenol, in the visible light [17]. Irokawa et al [18] have reported that in the presence of visible light, toluene, which was weakly adsorbed on the surface of the catalyst, was initially photo-oxidised to products like benzaldehyde, which then strongly adsorbed on to the surface of the catalyst and resulted in products like aldehydes. These products are then photo degraded to CO 2 and H 2 O under visible light irradiation.…”
Section: B Photocatalytic Degradation Of Target Vocs With Nitrogen Dmentioning
confidence: 99%